The predictive role of the hs-CRP/HDL-C ratio for long-term mortality in the general population: evidence from a cohort study - Yifeng Wang; Li Wang; Zongquan Zhao; Song Yin; Xuejun Tang; Kerui Zhang (BMC Cardiovascular Disorders)
Abstract Background The high-sensitivity C-reactive protein (hs-CRP) to high-density lipoprotein cholesterol (HDL-C) ratio, a composite marker of low-grade inflammation and lipid metabolism, is reportedly associated with the occurrence of new cardiovascular diseases (CVDs) in certain people. However, the predictive value of the hs-CRP/HDL-C ratio for long-term mortality in the general population remains unclear. Methods This retrospective cohort study included data from 9,492 adults obtained from the National Health and Nutrition Examination Survey (NHANES) (2015–2018) in the United States. Multivariate Cox regression, two-piecewise linear regression, restricted cubic spline (RCS) models and subgroup analysis by age, sex, smoking status and drinking status were applied to evaluate the associations of the hs-CRP/HDL-C ratio with long-term all-cause and cardiovascular mortality. Results The overall median age of the cohort was 47.0 years (interquartile range (IQR) 32.0–62.0), and 4,585 (48.30%) patients were male. During a median follow-up period of 37.0 months, 239 (2.52%) all-cause deaths occurred, 59 (0.62%) of which were attributed to cardiovascular events. Participants with all-cause and cardiovascular mortality presented a higher hs-CRP/HDL-C ratio than did those without events [0.56 (0.24–1.38) vs. 0.37 (0.14–0.94) and 0.60 (0.23–1.60) vs. 0.37 (0.14–0.95), P < 0.001 and P = 0.002]. According to multivariate Cox regression models, the hs-CRP/HDL-C ratio was found to be an independent risk factor for both long-term all-cause mortality [hazard ratio (HR) = 1.09, 95% confidence interval (CI): 1.05–1.13] and cardiovascular mortality (HR = 1.11, 95% CI: 1.05–1.19). A two-piecewise linear regression model indicated that the risk of all-cause mortality increased more prominently when the hs-CRP/HDL-C ratio was less than 1.21. In addition, a significant interaction effect with smoking status was discovered (P = 0.006), indicating that the association of the hs-CRP/HDL-C ratio with all-cause mortality was stronger in nonsmokers. The RCS curve revealed a positive linear association of the hs-CRP/HDL-C ratio with long-term mortality after adjustment for potential confounders. Conclusions The hs-CRP/HDL-C ratio is a crucial predictor of long-term mortality in the general population, independent of potential confounding factors.